Design of bearingless centrifugal blood pump - Wan, Song (2008)
Conventional centrifugal blood pumps have many disadvantages. The major drawback comes from the mechanical bearings. Blood tends to clot at mechanical bearings leading to thromboembolism, a serious medical condition of obstruction of blood vessels by clots. Other disadvantages include bulky structure and low efficiency. So the idea of a pump with no mechanical bearing is proposed. Therefore in this project, my objective is to investigate the feasibility of a novel design of a pump with no mechanical bearings, with a dual-stator, double-sided disk rotor structure which combines motor, pump impellor, and magnetic bearings into an integrated unit. In this project, the feasibility of this novel concept of centrifugal blood pump without mechanical bearings was investigated by simulations and experiments. The adoption of brushless DC (BLDC) motor with axial flux structure makes the axial magnetic suspension feasible and possible to be implemented. The double stator structure produces higher torque compared to conventional BLDC motor, besides enabling control of axial levitation. In order to control the other degrees of freedom easily and to make structure compact, a system of passive repulsive type of magnetic bearings was also proposed and integrated into the system.